2021
DOI: 10.1007/s00259-021-05362-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of [18F]FDG-PET/CT for treatment monitoring in large vessel vasculitis: a systematic review and meta-analysis

Abstract: Purpose Monitoring disease activity in patients with large vessel vasculitis (LVV) can be challenging. [18F]FDG-PET/CT is increasingly used to evaluate treatment response in LVV. In this systematic review and meta-analysis, we aimed to summarize the current evidence on the value of [18F]FDG-PET/CT for treatment monitoring in LVV. Methods PubMed/MEDLINE and the Cochrane library database were searched from inception through October 21, 2020. Studies containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 44 publications
2
52
0
1
Order By: Relevance
“…However, with the jugular vein serving as a reference, similar results were obtained (Supplementary Materials Figure S1), further demonstrating that blood pool and liver may be suitable for calculation of target-to-background ratios in the context of GCA/PMR, which is in line with recommendations of current guidelines [8]. Nonetheless, a recent meta-analysis demonstrated that [ 18 F]FDG had only moderate accuracy in detecting active sites of disease in LVV, thereby indicating that PET-based findings should be carefully interpreted in the context of clinical and laboratory parameters [35]. As such, the results of the present proof-of-concept study and herein provided ratios must definitely be confirmed in larger prospective, multi-centric settings, preferably by using phantom studies to provide harmonized semi-quantitative values among multiple PET centers [36].…”
Section: Discussionsupporting
confidence: 77%
“…However, with the jugular vein serving as a reference, similar results were obtained (Supplementary Materials Figure S1), further demonstrating that blood pool and liver may be suitable for calculation of target-to-background ratios in the context of GCA/PMR, which is in line with recommendations of current guidelines [8]. Nonetheless, a recent meta-analysis demonstrated that [ 18 F]FDG had only moderate accuracy in detecting active sites of disease in LVV, thereby indicating that PET-based findings should be carefully interpreted in the context of clinical and laboratory parameters [35]. As such, the results of the present proof-of-concept study and herein provided ratios must definitely be confirmed in larger prospective, multi-centric settings, preferably by using phantom studies to provide harmonized semi-quantitative values among multiple PET centers [36].…”
Section: Discussionsupporting
confidence: 77%
“…In these trials, consistency and congruency of imaging characteristics are of utmost importance since patients are often imaged at different time points or during treatment. Indeed, a recent systematic review suggested that TBR-based semi-quantitative indices might potentially be more responsive to change than composite scores based on visual assessment [ 36 ]. The best parameter to be applied in clinical studies is yet to be determined, and well-designed clinical trials may provide an answer to the value and indication of quantitative PET in LVV.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, imaging techniques such as ultrasonography, detecting the "halo" sign in inflamed cranial and axillary arteries of GCA patients, and 18 F-Fluorodeoxyglucose PET/CT (FDG-PET/CT) are emerging as more sensitive and specific diagnostic tools for GCA [97][98][99]. Although vasculitic lesions as detected by these imaging methods often improve upon treatment-induced remission, vascular abnormalities may still persist despite clinical remission [100,101]. This observation could reflect ongoing smoldering inflammation in the vessel or perhaps post-inflammatory vascular remodeling.…”
Section: Macrophage Related Biomarkers As a Tool For Gca Diagnosis And Disease Monitoringmentioning
confidence: 99%
“…Apart from blood biomarkers, positron emission tomography combined with computed tomography (PET/CT) is emerging as a potent diagnostic tool for GCA. Visualization of inflammation via [ 18 F]FDG-PET imaging is now a useful tool for diagnosis and monitoring of treatment in GCA [101]. However, [ 18 F]FDG-PET imaging still shows a number of disadvantages.…”
Section: B Macrophage Targeted Imagingmentioning
confidence: 99%
See 1 more Smart Citation